The impact of sports participation on cognitive functions and academic performance among youth aged 10 to 14 years: A comprehensive investigation (Research, Society and Development, 2024)
Sports practice is essential for young people to perform better in the various pillars of their lives. Considering the maturational stage, this study aimed to investigate the effects of practicing sports on cognitive aspects (inhibitory control) and academic performance (report card).Seventy-five young people aged between 10 and 14 of both sexes were analyzed and divided into two groups: group I (Non-sporty), involved only in school physical education, and group II (Sporty), involved in sports initiation in addition to school physical education. Inhibitory control was assessed using the Go/No Go test and the 5-digit test (FDT). Maturation was determined using the bone age equation, and academic performance was assessed on the basis of school report card grades. There were no significant correlations between bone age, performance on cognitive tests and academic performance based on report card grades (p ≥ 0.05). However, the cognitive tests revealed a significant disparity between the two groups. The sportsmen had significantly fewer errors in all phases of the FDT test (p < 0.05) than their non-sporting peers. In addition, the sports group showed superior inhibitory control, as evidenced by better performance in the Go/No Go test [7.58 ± 0.14; p = 0.001]. It is concluded that regardless of the correlation between maturational development, cognitive aspects and academic performance, systematized sports practice has a beneficial effect on the cognitive abilities of young people, since sports players showed better cognitive performance than non-sports players.